Contoh implementasi metode iqra dalam pembelajaran al-qur’an di TPQ se kecamatan Diwek: Contoh implementasi metode iqra dalam pembelajaran al-qur’an di TPQ se kecamatan Diwek - Hamdi, Ali; Hamdi, Ali (Maliki Interdisciplinary Journal, 2024)
This study aims to improve the ability to read the Qur’an through the Iqra’ method at TPQ in Diwek District. Interactive methods including imitation, viewing of lip movements, clear communication, and discussion are used. Daily learning with tiered material in Iqra’ volumes. Evaluation includes the initial, daily, and volume increase stages. The evaluation results showed a significant increase in students’ Al-Qur’an reading ability. An interactive approach and systematic materials contribute to satisfying results. In journal writing, researchers use a qualitative approach and use literature study methods or conduct studies of several scientific works that are used as material in making this journal. This journal writing also uses data collection techniques taken from interviews by several informants, journals, the internet, as well as readings relevant to the title. Suggestions include qualified teachers, emphasizing faith and morals, wise technology integration, the role of parents, and follow-up programs. It is hoped that the effective Iqra’ method and sustainable development can bring young people closer to the Al-Qur’an and its benefits.